Skin and Soft Tissue Infections Caused by Mycobacterium chelonae: More Common Than Expected? - Ugur Uslu; Olga Böhm; Franz Heppt; Michael Sticherling (Medical Journals Sweden, 2019)
Mycobacterium chelonae is a rapidly growing non-tuberculous mycobacterium, which causes infections of the human skin and soft tissue. Despite an increasing incidence of such infections, patients are often misdiagnosed. We report here 5 patients with cutaneous and/or soft tissue infection due to M. chelonae who were diagnosed and treated at our centre. Two of the 5 patients were on immunosuppressive treatment. While clinical presentations differed in each patient, all had a long history of skin lesions. In addition to careful history-taking, tissue biopsies were obtained for mycobacterial culture and histopathological examination. Culture-directed antibiotic therapy was initiated, which resulted in a slow, but continuous, healing of the lesions. In summary, M. chelonae infections are still relatively rare, but should be considered in both immunocompromised and immunocompetent patients with prolonged skin lesions resistant to standard antibiotic treatment. For diagnosis, tissue analysis for mycobacterial culture and histopathological examination, and once diagnosed, adequate antibiotic treatment, is needed.